Improving Health Literacy for People with Low Literacy - Mbanda, Njabulo Mary-Louise (UJ Press, 2024)
Health literacy and low health literacy have received increased attention due to their association with poor understanding of health information, and consequently negative health outcomes. Although much research discusses health literacy and its role; there are gaps in explaining the relationship between health literacy and low literacy; as well as various determinants of health (i.e., social, cultural, political, etc.). This relationship is particularly significant for lower- and middle-income countries where most clients might not even speak English as a first language or the same language of the health care providers.